2011
DOI: 10.1038/jid.2010.415
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte Secretion of Cyclophilin B via the Constitutive Pathway Is Regulated through Its Cyclosporin-Binding Site

Abstract: Cyclophilin B (CypB) is an endoplasmic reticulum (ER)-resident member of the cyclophilin family of proteins that bind cyclosporin A (CsA). We report that as in other cell types, CypB trafficked from the ER and was secreted by keratinocytes into the media in response to CsA. Concentrations as low as 1 p of CsA induced secretion of CypB. Using brefeldin A, we showed that CypB is secreted from keratinocytes via the constitutive secretory pathway. We defined that substitution of tryptophan residue 128 in the CsA-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 49 publications
3
18
0
Order By: Relevance
“…Neither CypB nor CypC contain a "KDEL-like" ER localization signal and previous reports have variously attributed a localization signal on CypB to its C-terminal 10 residues (45) or to a Trp residue within the CsA binding site (46). Consistent with the latter finding, it has been reported that CsA treatment induces CypB secretion from the ER to the media in HeLa and BHK cells (27).…”
Section: Cyclophilin C Resides Within the Early Secretory Pathway-supporting
confidence: 76%
See 1 more Smart Citation
“…Neither CypB nor CypC contain a "KDEL-like" ER localization signal and previous reports have variously attributed a localization signal on CypB to its C-terminal 10 residues (45) or to a Trp residue within the CsA binding site (46). Consistent with the latter finding, it has been reported that CsA treatment induces CypB secretion from the ER to the media in HeLa and BHK cells (27).…”
Section: Cyclophilin C Resides Within the Early Secretory Pathway-supporting
confidence: 76%
“…Neither protein possesses a canonical ER localization sequence, but CypB retention in the ER has been suggested to be conferred by a novel C-terminal motif (VEKP-FAIAKE) (45). Alternatively, because CsA treatment induces CypB (27) and, as shown here, CypC secretion, it has been suggested that ER localization of CypB is regulated through its CsA binding site (46). However, mutations within either region did not substantially alter its ER distribution.…”
Section: Discussionmentioning
confidence: 75%
“…The mechanism of CypA secretion is largely unknown, although it may involve vesicular transport (40). The related cyclophilin B can also be secreted via targeting through the endoplasmic reticulum with an N-terminal signal sequence (41,42). It is unknown if Cyp19 is destined for secretion using an N-terminal signal sequence, although it possesses a 10-residue N-terminal region not found in human CypA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although cytosolic, CyPA can be secreted by macrophages and vascular smooth muscle cells in response to LPS and oxidative stress (14,15). Unlike CyPA, CyPB is constitutively secreted by tissueresident cells (e.g., fibroblasts, chondrocytes, and keratinocytes) and accumulates within the extracellular matrix (16)(17)(18). Importantly, it is released intact by heparanase and matrix metalloproteinases (MMPs), suggesting that it can participate in tissue inflammation.…”
mentioning
confidence: 99%